Regional financial integration in the Caribbean : evidence from financial and macroeconomic data - Espinoza, Raphael (IMF [Washington]US, 2009)
Assesses the extent of financial integration in the Caribbean Community by analyzing equity prices in the region and rigidity of external financing constraints.